Getting a Handle on Sales: Shopping Carts Affect Purchasing by Activating Arm Muscles - Estes, Zachary; Streicher, Mathias C. (Journal of Marketing, 2022)
This research demonstrates that the physical properties of shopping carts influence purchasing and spending. Prior research on ergonomics indicates that standard shopping carts, which are pushed via a horizontal handlebar, are likely to activate arm extensor muscles. Prior research on arm muscle activation, in turn, suggests that arm extensor activation may elicit less purchasing than arm flexor activation. The authors thus deduce that standard shopping carts may be suboptimal for stimulating purchases. The authors predicted that shopping carts with parallel handles (such as on a wheelbarrow or “walker”) would instead activate the flexor muscles and thus increase purchasing. An electromyography study revealed that both horizontal and vertical handles more strongly activate the extensor muscles of the upper arm (triceps), whereas parallel handles more strongly activate the flexor muscles (biceps). In a field experiment, parallel-handle shopping carts significantly and substantially increased sales across a broad range of categories, including both vice and virtue products. Finally, in a simulated shopping experiment, parallel handles increased purchasing and spending beyond both horizontal and vertical handles. These results were not attributable to the novelty of the shopping cart itself, participants’ mood, or purely ergonomic factors.